The Relationship Between School Culture and Student Achievement in High School - Santia Santia; Budi Astuti; Deananda Syafitri (Journal of Innovation in Educational and Cultural Research)
Background on school culture is one factor that influences students to improve learning achievement at school. A healthy school culture provides opportunities for school members to function optimally, work efficiently, be full of vitality, have high spirits, and be able to continue to grow. This research aims to collect empirical evidence or facts about the relationship between school culture and student achievement by looking at the influence between school culture and student achievement. This research methodology uses a quantitative approach with a correlational research design. Because the data distribution is close to the normal curve, the sample of this research consists of 112 students. The results showed a highly significant relationship with a positive correlation level of 0.812. This research concludes that school culture and student learning achievement have a significant positive relationship. This research makes an important contribution by showing how school culture affects student achievement at the secondary school level. The results reinforce the understanding that a positive and supportive school environment can improve student motivation, engagement, and learning outcomes.